Anti-burst glass bottle and preparation process thereof

By adopting a multi-layer structure of endoderm body, intermediate layer and protective layer, and using the combination and process of specific materials, the problem of insufficient explosion-proof performance of glass bottles is solved, and efficient impact and explosion-proof effects are achieved, which improves safety and simplifies the production process.

CN119797761APending Publication Date: 2025-04-11PUTIAN RIJING GLASS PROD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510028890.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The explosion-proof performance of existing glass bottles is insufficient and it is prone to rupture when impacted, causing glass fragments to scatter and cause personal injury. The existing explosion-proof glass is cumbersome and resources are wasted, and the anti-fall effect of the protective cover weakens with the use time.

Method used

The endoderm body, intermediate layer and protective layer structure are adopted from the inside to the outside. The endoderm body is made of cordierite, bismuth oxide and AIN ceramic powder. The intermediate layer contains aluminum silicate fibers, polyethylene fibers and silica aerogel. The protective layer is composed of wollastonite glass powder and fluorapatite glass powder. Through the combination and process of these materials, a strong and crack-resistant structure is formed.

Benefits of technology

It significantly improves the impact and burst resistance of glass bottles, reduces the splash of glass fragments, improves the safety of use, and simplifies the production process, avoids waste of resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005233587240000121
    Figure BDA0005233587240000121
Patent Text Reader

Abstract

The invention relates to the field of glass product processing, and particularly discloses an anti-burst glass bottle and a preparation process thereof. The anti-burst glass bottle comprises an inner blank body, a middle layer and a protective layer which are sequentially contacted from inside to outside, and the inner blank body is prepared from the following raw materials: cordierite, bismuth oxide and AIN ceramic powder in a mass ratio of 1: (0.03-0.05): (0.2-0.4); the middle layer comprises the following raw materials: aluminum silicate fiber, polyethylene fiber and silicon dioxide aerogel in a mass ratio of 1: (0.3-0.4): (10-15); the protective layer comprises the following raw materials: wollastonite glass powder and fluorapatite glass powder in a mass ratio of 1: (0.2-0.3). The anti-burst glass bottle has the advantages that the anti-burst effect is good, the splashing condition of broken glass fragments is reduced, and the safety is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of glass product processing, and more specifically, to an explosion-proof glass bottle and a preparation process thereof. Background Art

[0002] Glass bottles are a kind of container with high strength but easy to break. Because of the characteristics of glass bottles such as stable shape, no odor, smooth surface, good barrier properties and beautiful appearance, glass bottles still occupy an important position in beverage packaging when many packaging materials are flooding into the market, and are deeply loved by consumers.

[0003] However, the explosion-proof performance of glass bottles is insufficient. When they are stood up, squeezed, hit, or dropped, they are easily broken. The broken glass bottles form multiple glass fragments and scatter in all directions. The scattered glass fragments can easily cause injuries.

[0004] In order to ensure the personal safety of users, most of the current explosion-proof glass is laminated glass, and the explosion-proof glass is an integrated structure of injection molding. During the production process, a film glue layer will be applied between the two layers of glass, so that the explosion-proof glass has good impact resistance, and at the same time, the toughness and resilience of the glass itself are enhanced. However, the production of explosion-proof glass is very cumbersome, requiring a lot of manpower and material resources, and the use of explosion-proof glass to make beverage bottles will cause resource waste and do not meet production requirements. The prior art also discloses the use of protective sleeves to reduce the bursting of glass bottles. The protective sleeves are mostly silicone sleeves or cotton sleeves. During the production process, ordinary glass bottles and protective sleeves with at least one opening are first mass-produced, and then the protective sleeves are set on the bottle body of the glass bottle. When the glass bottle falls or is impacted, the protective sleeve can provide a buffering effect for the glass bottle, thereby achieving the purpose of explosion-proof. However, although the production cost of the protective sleeve is not high, there is a gap between the protective sleeve and the glass bottle. As the use time increases and the gap continues to increase, the anti-fall effect of the protective sleeve will gradually weaken, resulting in low practicality of the glass bottle. Therefore, it is urgent to develop an explosion-proof glass bottle with good explosion-proof effect and simple manufacturing method. Summary of the invention

[0005] In order to improve the explosion-proof capability of glass bottles and increase the safety of use, the present application provides an explosion-proof glass bottle and a preparation process thereof.

[0006] In a first aspect, the present application provides an explosion-proof glass bottle, which adopts the following technical solution: An explosion-proof glass bottle comprises an endomorph, an intermediate layer and a protective layer which are contacted from the inside to the outside in sequence, wherein the raw materials of the endomorph comprise cordierite, bismuth oxide and AIN ceramic powder in a mass ratio of 1:0.03-0.05:0.2-0.4; The raw materials of the middle layer include aluminum silicate fiber, polyethylene fiber and silica aerogel in a mass ratio of 1:0.3-0.4:10-15; The raw materials of the protective layer include wollastonite glass powder and fluoroapatite glass powder in a mass ratio of 1:0.2-0.3.

[0007] By adopting the above technical scheme, wollastonite glass powder is used as the base phase, and fluoroapatite glass powder is used as the second phase. In the base phase, microspheres are precipitated with larger wollastonite crystals. The larger wollastonite is intermixed to make more glass phases between the crystal gaps. The combination of glass and crystals is not enough to overcome the disadvantage of large intervals. Therefore, fine fluoroapatite glass powder is added. The fine fluoroapatite crystal phase can precipitate and grow in an interlaced manner with the wollastonite crystal phase to form a structure that is complementary in size and relatively dense, which can effectively prevent the generation and expansion of cracks in the protective layer, make the glass bottle have stronger toughness, and improve its crack resistance. Therefore, as the outermost protective layer, it can give the glass bottle stronger crack resistance and impact resistance.

[0008] Cordierite, bismuth oxide and AIN ceramic powder are used as the endomorph. When the blend is sintered, the viscous flow energy of the liquid phase promotes the bonding and aggregation between the powder particles, so that the gas is expelled along the grain boundary or closed pores are formed between the grains, thereby densifying the endomorph. In addition, bismuth oxide is a fusible oxide with a low melting point, so the cordierite with bismuth oxide added has a low soft spot and a low viscosity, which promotes the sintering densification of the protective layer, thereby obtaining an endomorph with strong density, strength and hardness.

[0009] Aluminum silicate fiber, polyethylene fiber and silica aerogel are used as the middle layer. Aluminum silicate fiber is made of high-purity alumina and silicon oxide crystals through a special process. It has excellent high temperature resistance and can work stably for a long time in a high temperature environment. It can withstand high temperatures of about 1000°C to 1400°C without obvious physical or chemical changes. Therefore, when the molten liquid glass is used to prepare the inner body and protective layer, the aluminum silicate fiber still maintains a high stability. In addition, the fibrous structure and excellent thermal stability of the aluminum silicate fiber give it a high anti-explosion ability, which can prevent heat conduction and reduce the thermal stress caused by the temperature gradient, thereby reducing the risk of explosion. The silica aerogel has a special nanoporous mesh structure inside, and the shock wave is transmitted to the aerogel through the aerogel. The propagation speed in silica aerogel is extremely low, so it can attenuate the propagation speed of shock waves in the middle layer. In addition, silica aerogel has extremely low density and thermal conductivity. Its unique nanoparticle skeleton and uniform pore size distribution give it a unique thermal insulation effect. It can block the heat transfer of the endoderm in the middle layer, thereby reducing the temperature gradient between the inside and outside and reducing the possibility of self-explosion of the glass bottle. Polyethylene fiber has a low melting point. After mixing it with aluminum silicate fiber, it can form a mesh structure that overlaps each other. After heating, it melts and has a strong bonding effect on the endoderm. Combined with the shock wave attenuation ability of silica aerogel and the mesh porous structure of aluminum silicate fiber, it can absorb and reduce impact energy and reduce the splashing problem caused by the glass bottle after breaking.

[0010] Optionally, the thickness ratio of the intermediate layer to the endoderm is 0.4-0.6:1.

[0011] By adopting the above technical scheme, the thickness of the protective layer formed by aluminum silicate fiber, polyethylene fiber and silica aerogel on the endoderm is less than the thickness of the endoderm. While not affecting the bonding tightness between the endoderm and the protective layer, it can provide the glass bottle with a strong shock wave absorption ability, reduce the splash of fragments, and improve the impact resistance and explosion resistance.

[0012] Optionally, the composition ratio of the fluoroapatite glass powder is as follows: 3.57 wt % sodium oxide, 16.12 wt % boron oxide, 26.64 wt % silicon dioxide, 30 wt % calcium oxide, 20 wt % phosphorus pentoxide and 3.66 wt % calcium fluoride.

[0013] Optionally, the composition ratio of the wollastonite glass powder is as follows: 10 wt % sodium oxide, 25 wt % calcium oxide and 65 wt % silicon dioxide.

[0014] By adopting the above technical scheme, silicon dioxide is the main component of the glass bottle, which can make the glass bottle have a series of excellent properties, such as good transparency, mechanical strength, chemical stability and thermal stability. However, the content of silicon dioxide in the glass bottle cannot exceed 80%. If it exceeds this value, the melt viscosity will be high, melting will be difficult, and the heat consumption will be large. If it is lower than this value, the transparency and mechanical strength of the glass bottle will be affected. Adding calcium oxide can appropriately reduce the high-temperature viscosity and promote the melting and clarification of the glass mixture. When the content is high, it will increase the crystallization tendency of the glass bottle, reduce the thermal stability of the glass bottle, and increase the annealing temperature. Sodium oxide is a good solvent, which reduces the viscosity of the glass, promotes the melting and clarification of the glass liquid, and can also greatly reduce the crystallization tendency of the glass bottle.

[0015] Optionally, the length of the polyethylene fiber is 10-12 mm, and the length of the aluminum silicate fiber is 15-20 mm.

[0016] By adopting the above technical scheme, the polyethylene fiber and the aluminum silicate fiber overlap each other, and the polyethylene fiber is hot-melted after hot melting, losing its fiber shape, but firmly bonded to the endoderm, and the aluminum silicate fiber and the silica aerogel are adhered to the endoderm to form an intermediate layer that can absorb shock waves and reduce the propagation speed of shock waves, thereby reducing the explosion of the glass bottle.

[0017] Optionally, phenolic fiber and low-melting-point glass powder are further added to the protective layer, and the mass ratio of the phenolic fiber, the low-melting-point glass powder and the wollastonite glass powder is 0.2-0.4:0.1-0.2:1.

[0018] By adopting the above technical scheme, phenolic fiber is made of phenolic resin through dissolution, electrostatic spinning and thermal curing. Phenolic resin is a thermosetting resin. The phenolic fiber made after spinning has excellent thermal insulation performance and extremely low thermal conductivity. It can reduce the temperature difference between the inside and the outside and reduce the temperature gradient. In addition, the phenolic fiber has good flexibility and mechanical properties. In the protective layer, it cooperates with the middle layer to further reduce the splash of fragments of the protective layer. The low-melting point glass powder has a low melting point of about 340°C and can be hot-melted at low temperatures to increase the bonding strength between the phenolic fiber and the protective layer. The phenolic fiber forms a mesh porous structure on the protective layer, which can reduce impact energy and reduce the splash of fragments, and at the same time improve the impact resistance and bending resistance of the glass bottle.

[0019] Optionally, the phenolic fiber is made by mixing phenolic resin, polyvinyl butyral and anhydrous ethanol in a mass ratio of 4:0.03-0.035:6-7, followed by electrostatic spinning and heating curing.

[0020] By adopting the above technical scheme, polyvinyl butyral is added to adjust the viscosity of the phenolic resin, so that after the phenolic resin is spun, fibers with uniform fineness and high aspect ratio are obtained, and after thermal curing, the heat resistance of the phenolic fiber is improved. Anhydrous ethanol is used as a solvent, which is non-toxic and harmless, and can effectively dissolve the phenolic resin without affecting the environment. In addition, the ethanol solvent evaporates quickly, eliminating the process of removing the solvent.

[0021] In a second aspect, the present application provides a process for preparing an explosion-proof glass bottle, which adopts the following technical solution: A preparation process of an explosion-proof glass bottle comprises the following steps: The cerium oxide and cordierite are melted at 1500-1560°C for 2-4 hours, quenched with water, dried, ball-milled, and sieved to obtain a powder, which is mixed with AIN ceramic powder and heated until melted to obtain a hot melt; The hot melt is poured into the mold, blown into shape, and annealed once to obtain an endoderm; The polyethylene fiber and the aluminum silicate fiber are mixed evenly and needle-punched to obtain a needle-punched felt, and the needle-punched felt is placed in a silica sol, supercritically dried, and crushed to obtain a fiber-reinforced aerogel powder; Spraying fiber-reinforced aerogel powder on the endoderm, heating to 140-160° C., and keeping the temperature for 2-4 hours to obtain an intermediate layer on the endoderm; The wollastonite glass powder and the fluoroapatite glass powder are uniformly mixed and heated until they are melted to obtain a melt; The melt is injected into the mold, and the endoderm with the middle layer is placed in the mold. The melt adheres to the middle layer, and then secondary annealing and cooling are performed to form a protective layer on the middle layer to produce an explosion-proof glass bottle.

[0022] By adopting the above technical solution, cerium oxide and cordierite are first heat-melted, which effectively reduces the temperature of the cordierite phase transition and promotes sintering density. Then, they are heat-melted with AIN glass powder to a liquid glass state, blown into shape, and annealed to obtain a high-density endoderm.

[0023] The needle-punched felt formed by mixing and needle-punching polyethylene fibers and aluminum silicate fibers is impregnated in silica sol. After supercritical drying, the silica sol forms silica aerogel, which adheres evenly around the fibers, reducing the gaps between the polyethylene fibers and the aluminum silicate fibers. At the same time, the fibers and gel particles are tightly combined, which helps to disperse the stress and enhance the strength of the needle-punched felt. The aluminum silicate fibers and polyethylene fibers serve as skeletons and are adhered to the silica aerogel. The fiber skeleton wrapped with the silica aerogel is sprayed on the endoderm. After heating, the polyethylene fibers are hot-melted and the aluminum silicate fibers are adhered to the endoderm as a skeleton, which makes the thermal conductivity lower, helps to reduce the collision frequency of air molecules, reduce heat conduction, reduce temperature gradients, and at the same time reduce impact energy and fragment splashing.

[0024] Then, wollastonite glass powder and fluoroapatite glass powder are mixed into a molten state, and the melt is adhered to the intermediate body of the endoderm. After annealing, a protective layer is obtained. The protective layer can be firmly attached to the intermediate layer to obtain a hard protective effect, while providing strong impact resistance and bending resistance.

[0025] Optionally, the polyethylene fiber and aluminum silicate fiber are subjected to the following pretreatment before needling: Add carboxymethyl cellulose to a mixture of anhydrous ethanol and distilled water, stir for 10-15 minutes, add polyvinyl alcohol, heat to 70-80°C, stir for 1-2 hours, and prepare a treatment solution; Add the uniformly mixed polyethylene fiber and aluminum silicate fiber to the treatment liquid, stir evenly, filter, and dry at 70-80°C for 8-10 hours. The mass ratio of aluminum silicate fiber to carboxymethyl cellulose is 1:0.5-0.625.

[0026] By adopting the above technical solution, carboxymethyl cellulose and polyvinyl alcohol are used to surface treat polyethylene fibers and aluminum silicate fibers, which can improve the interface bonding effect between the fibers and the glass matrix, increase the adhesion and wettability of the protective layer on the endoderm, increase the bonding strength, and improve the overall performance.

[0027] Optionally, before the melt is injected into the mold, evenly mixed phenolic fiber and low-melting point glass powder are sprayed onto the inner surface of the mold, and the mass ratio of phenolic fiber, low-melting point glass powder and wollastonite glass powder is 0.2-0.4:0.1-0.2:1.

[0028] By adopting the above technical scheme, the phenolic fiber and the low-melting-point glass powder are evenly mixed, sprayed into a mold, and then injected into a melt. The high temperature of the melt can cause the low-melting-point glass powder to gradually melt, thereby bonding the phenolic fiber to the melt, increasing the adhesion strength between the phenolic fiber and the melt, thereby forming a phenolic fiber network on the outside of the melt. The phenolic fiber is a thermosetting material with good heat resistance. It can form a three-dimensional network structure that overlaps each other on the glass formed by the melt, thereby protecting the glass formed by the melt; the high temperature of the melt may also cause partial carbonization of the phenolic fiber, but the carbonized phenolic fiber still has strong mechanical strength, and has very high strength and modulus, so that it can maintain good stability when subjected to heavy pressure and impact.

[0029] Optionally, the surface density of the needle felt is 180-200 g / m 2 .

[0030] By adopting the above technical scheme, the needle-punched felt with the above density can have good impact protection performance and good penetration energy absorption performance when subjected to explosion impact stress. Therefore, it is less likely to break when subjected to high-speed impact, thereby improving the impact resistance and explosion-proof effect of the glass bottle.

[0031] Optionally, the secondary annealing process is: keeping at 550-600°C for 15-20min, then cooling to 300-350°C at a rate of 4-8°C / min, keeping for 120-200min, cooling to 150-200°C at a rate of 4-8°C / min, keeping for 60-80min, and finally cooling to 100-130°C at a rate of 4-8°C / min, keeping for 120-180min.

[0032] By adopting the above technical solution, the gradual annealing temperature and time of the glass bottle are controlled, so that the internal stress of the glass bottle is released, the brittleness of the glass bottle is effectively reduced, and its mechanical strength and toughness are improved. Therefore, the glass bottle is less likely to break when subjected to external force, reducing the risk of self-explosion. It also reduces the thermal expansion coefficient of the glass bottle, making it more heat-resistant, and the internal stress changes more gently, reducing the risk of cracking caused by temperature stress.

[0033] In summary, this application has the following beneficial effects: 1. Since the present application uses cordierite, cerium oxide and AIN ceramic powder to prepare an endomorph with high hardness and good density, and uses wollastonite glass powder and fluoroapatite glass powder to prepare a protective layer with strong toughness and capable of preventing the generation and development of cracks, an intermediate layer with strong bonding strength with the protective layer and the endomorph is arranged between the protective layer and the endomorph, and the intermediate layer contains aluminum silicate fiber, polyethylene fiber and silica aerogel, which can effectively slow down the transmission of shock waves, increase the anti-explosion effect, reduce the splash of fragments, and improve safety.

[0034] 2. The method of the present application is as follows: aluminum silicate fiber and polyethylene fiber are mixed, impregnated with silica sol after needle punching, supercritically dried, crushed, and sprayed on the endoderm; after heating, the polyethylene fiber is heat-melted, and the aluminum silicate fiber is adhered to the endoderm as a skeleton, and the aluminum silicate fiber is adhered to the silica aerogel, thereby further reducing the transmission of shock waves, reducing the temperature gradient, reducing the self-explosion rate, and reducing the splashing of glass fragments.

[0035] 3. According to the method of the present application, wollastonite glass powder and fluoroapatite glass powder are hot-melted into a melt. Before being injected into the mold, phenolic fiber and low-melting-point glass powder are first sprayed. Then the melt is injected and an inner embryo with an intermediate layer is placed. The low-melting-point glass powder gradually melts due to the high temperature of the melt, connecting the phenolic fiber to the melt. The melt forms a protective layer on the intermediate layer. The phenolic fiber can further reduce the splashing of the protective layer when it is broken, thereby improving safety and the impact resistance of the glass bottle. DETAILED DESCRIPTION

[0036] The following examples further illustrate the present application in detail. Example

[0037] Embodiment 1: An explosion-proof glass bottle, comprising an endomorph, an intermediate layer and a protective layer contacting each other from the inside to the outside, wherein the raw materials of the endomorph comprise cordierite, bismuth oxide and AIN ceramic powder in a mass ratio of 1:0.03:0.4, the cordierite comprises 13.8wt% magnesium oxide, 34.9wt% aluminum oxide and 51.3wt% silicon dioxide, and the AIN ceramic powder is selected from Qinghe County Beiyan Metal Material, with a grade of AI-1; The thickness ratio of the middle layer to the inner body is 0.6:1. The raw materials of the middle layer include aluminum silicate fiber, polyethylene fiber and silica aerogel in a mass ratio of 1:0.4:15. The polyethylene fiber is selected from Shandong OUDE Chemical Fiber Products, with a product number of PE450 and a length of 12 mm. The aluminum silicate fiber is selected from Lingshou County Tuyun Mineral Products, with a model of HP-2 and a length of 15 mm. The raw materials of the protective layer include wollastonite glass powder and fluoroapatite glass powder in a mass ratio of 1:0.3. The wollastonite glass powder is prepared by mixing 10wt% sodium oxide, 25wt% calcium oxide and 65wt% silicon dioxide, heating to 1540°C at 10°C / min, keeping the temperature for 1h, quenching with water, grinding and passing through a 200-mesh sieve. The fluoroapatite glass powder is prepared by mixing 3.57wt% sodium oxide, 16.12wt% boron oxide, 26.64wt% silicon dioxide, 30wt% calcium oxide, 20wt% phosphorus pentoxide and 3.66wt% calcium fluoride, heating to 1560°C at 10°C / min, keeping the temperature for 1h, quenching with water, grinding and passing through a 200-mesh sieve.

[0038] The preparation process of the explosion-proof glass bottle comprises the following steps: S1. Melt cerium oxide and 10 g of cordierite at 1500°C for 4 hours, then quench with water into small particles, dry and crush through a 50-mesh sieve, put the glass particles under the sieve into a ball mill, use ethanol as a ball milling aid, ball mill for 50 hours, dry and pass through a 100-mesh sieve, then mix evenly with a 5wt% polyvinyl alcohol solution, dry and pass through a 50-mesh sieve to obtain a powder, mix the powder with AIN ceramic powder, heat to 1560°C, keep warm for 2 hours, and obtain a hot melt; S2, pouring the hot melt into the mold, blowing it into shape, and annealing it once to obtain an endometrium. The annealing process is as follows: cooling to 600°C at 10°C / min, keeping warm for 20min, cooling to 400°C at 10°C / min, keeping warm for 120min, cooling to 150°C at 10°C / min, keeping warm for 80min, cooling to 100°C at 10°C / min, keeping warm for 120min; S3, evenly mix tetraethyl orthosilicate and ethanol to obtain liquid A with a concentration of 0.5 mol / l of tetraethyl orthosilicate, evenly mix ammonia water and ethanol to obtain liquid B with a concentration of 0.8 mol / l of ammonia water, mix liquid A and liquid B, react at 25°C for 4 hours, and then age at 60°C for 24 hours to obtain silica sol; evenly mix polyethylene fiber and 10g of aluminum silicate fiber and then needle-punch to obtain a sol with a surface density of 200g / m 2 , placing the needle felt in silica sol, supercritical drying, and crushing to obtain fiber-reinforced aerogel powder, with a supercritical pressure of 12 MPa and a supercritical temperature of 270°C; S4, spraying the fiber-reinforced aerogel powder on the endoderm, raising the temperature to 160° C., and keeping the temperature for 2 hours to obtain an intermediate layer on the endoderm, and the spraying amount of the fiber-reinforced aerogel powder is such that the thickness of the intermediate layer is 0.6 of the thickness of the endoderm; S5, mixing 10 g of wollastonite glass powder and fluoroapatite glass powder in a mass ratio, and heating until melted to obtain a melt; S6. Inject the melt into the mold, put the inner body with the intermediate into the mold, the melt adheres to the middle layer, and then perform secondary annealing and cooling to form a protective layer on the middle layer to obtain an explosion-proof glass bottle. The secondary annealing process is: keep warm at 550°C for 20 minutes, then cool down to 300°C at a rate of 8°C / min, keep warm for 200 minutes, cool down to 150°C at a rate of 8°C / min, keep warm for 80 minutes, and finally cool down to 100°C at a rate of 8°C / min, and keep warm for 180 minutes.

[0039] Embodiment 2: An explosion-proof glass bottle, comprising an endomorph, an intermediate layer and a protective layer contacting each other from the inside to the outside, wherein the raw materials of the endomorph comprise cordierite, bismuth oxide and AIN ceramic powder in a mass ratio of 1:0.05:0.2, the cordierite comprises 13.8wt% magnesium oxide, 34.9wt% aluminum oxide and 51.3wt% silicon dioxide, and the AIN ceramic powder is selected from Qinghe County Beiyan Metal Materials, with a grade of AI-1; The thickness ratio of the middle layer to the inner body is 0.4:1. The raw materials of the middle layer include aluminum silicate fiber, polyethylene fiber and silica aerogel in a mass ratio of 1:0.3:10. The polyethylene fiber is selected from Shandong OUDE Chemical Fiber Products, with a product number of PE450 and a length of 12 mm. The aluminum silicate fiber is selected from Lingshou County Tuyun Mineral Products, with a model of HP-2 and a length of 15 mm. The raw materials of the protective layer include wollastonite glass powder and fluoroapatite glass powder in a mass ratio of 1:0.2. The wollastonite glass powder is prepared by mixing 10wt% sodium oxide, 25wt% calcium oxide and 65wt% silicon dioxide, heating to 1540°C at 10°C / min, keeping the temperature for 1h, quenching with water, grinding and passing through a 200-mesh sieve. The fluoroapatite glass powder is prepared by mixing 3.57wt% sodium oxide, 16.12wt% boron oxide, 26.64wt% silicon dioxide, 30wt% calcium oxide, 20wt% phosphorus pentoxide and 3.66wt% calcium fluoride, heating to 1560°C at 10°C / min, keeping the temperature for 1h, quenching with water, grinding and passing through a 200-mesh sieve.

[0040] The preparation process of the explosion-proof glass bottle comprises the following steps: S1. Melt cerium oxide and 10 g of cordierite at 1560°C for 2 h, then quench with water into small particles, dry and crush through a 50-mesh sieve, put the glass particles under the sieve into a ball mill, use ethanol as a ball milling aid, ball mill for 50 h, dry and pass through a 100-mesh sieve, then mix evenly with a 5wt% polyvinyl alcohol solution, dry and pass through a 50-mesh sieve to obtain a powder, mix the powder with AIN ceramic powder, heat to 1560°C, keep warm for 2 h, and obtain a hot melt; S2, pouring the hot melt into the mold, blowing it into shape, and annealing it once to obtain an endoderm, the annealing process is: cooling to 580°C at 8°C / min, keeping warm for 25min, cooling to 350°C at 8°C / min, keeping warm for 160min, cooling to 130°C at 8°C / min, keeping warm for 100min, cooling to 120°C at 8°C / min, keeping warm for 100min; S3, evenly mix tetraethyl orthosilicate and ethanol to obtain liquid A with a concentration of 0.5 mol / l of tetraethyl orthosilicate, evenly mix ammonia water and ethanol to obtain liquid B with a concentration of 0.8 mol / l of ammonia water, mix liquid A and liquid B, react at 25°C for 4 hours, and then age at 60°C for 24 hours to obtain silica sol; evenly mix polyethylene fiber and 10g of aluminum silicate fiber and then needle-punch to obtain a silica sol with a surface density of 180g / m 2 , placing the needle felt in silica sol, supercritical drying, and crushing to obtain fiber-reinforced aerogel powder with a supercritical pressure of 12 MPa and a supercritical temperature of 270°C; S4, spraying fiber-reinforced aerogel powder on the endoderm, raising the temperature to 140° C., and keeping the temperature for 4 hours to obtain an intermediate layer on the endoderm, and the spraying amount of the fiber-reinforced aerogel powder is such that the thickness of the intermediate layer is 0.4 of the thickness of the endoderm; S5, mixing 10 g of wollastonite glass powder and fluoroapatite glass powder in a mass ratio, and heating until melted to obtain a melt; S6. Inject the melt into the mold, put the inner body with the intermediate into the mold, and the melt adheres to the middle layer, and then perform secondary annealing and cooling to form a protective layer on the middle layer to obtain an explosion-proof glass bottle. The secondary annealing process is: keep warm at 600°C for 15 minutes, then cool down to 350°C at a rate of 4°C / min, keep warm for 120 minutes, cool down to 200°C at a rate of 4°C / min, keep warm for 60 minutes, and finally cool down to 130°C at a rate of 4°C / min, and keep warm for 120 minutes.

[0041] Embodiment 3: An explosion-proof glass bottle, comprising an endomorph, an intermediate layer and a protective layer contacting each other from the inside to the outside, wherein the raw materials of the endomorph comprise cordierite, bismuth oxide and AIN ceramic powder in a mass ratio of 1:0.04:0.3, the cordierite comprises 13.8wt% magnesium oxide, 34.9wt% aluminum oxide and 51.3wt% silicon dioxide, and the AIN ceramic powder is selected from Qinghe County Beiyan Metal Materials, with a grade of AI-1; The thickness ratio of the middle layer to the inner body is 0.5:1. The raw materials of the middle layer include aluminum silicate fiber, polyethylene fiber and silica aerogel in a mass ratio of 1:0.4:12. The polyethylene fiber is selected from Shandong OUDE Chemical Fiber Products, with a product number of PE450 and a length of 12 mm. The aluminum silicate fiber is selected from Lingshou County Tuyun Mineral Products, with a model of HP-2 and a length of 15 mm. The raw materials of the protective layer include wollastonite glass powder and fluoroapatite glass powder in a mass ratio of 1:0.25. The wollastonite glass powder is prepared by mixing 10wt% sodium oxide, 25wt% calcium oxide and 65wt% silicon dioxide, heating to 1540°C at 10°C / min, keeping the temperature for 1h, quenching with water, grinding and passing through a 200-mesh sieve. The fluoroapatite glass powder is prepared by mixing 3.57wt% sodium oxide, 16.12wt% boron oxide, 26.64wt% silicon dioxide, 30wt% calcium oxide, 20wt% phosphorus pentoxide and 3.66wt% calcium fluoride, heating to 1560°C at 10°C / min, keeping the temperature for 1h, quenching with water, grinding and passing through a 200-mesh sieve.

[0042] The preparation process of the explosion-proof glass bottle comprises the following steps: S1. Melt cerium oxide and 10 g of cordierite at 1540°C for 3 hours, then quench with water into small particles, dry and crush through a 50-mesh sieve, put the glass particles under the sieve into a ball mill, use ethanol as a ball milling aid, ball mill for 50 hours, dry and pass through a 100-mesh sieve, then mix evenly with a 5wt% polyvinyl alcohol solution, dry and pass through a 50-mesh sieve to obtain a powder, mix the powder with AIN ceramic powder, heat to 1560°C, keep warm for 2 hours, and obtain a hot melt; S2, pouring the hot melt into the mold, blowing it into shape, and annealing it once to obtain an endometrium. The annealing process is as follows: cooling to 600°C at 10°C / min, keeping warm for 20min, cooling to 400°C at 10°C / min, keeping warm for 120min, cooling to 150°C at 10°C / min, keeping warm for 80min, cooling to 100°C at 10°C / min, keeping warm for 120min; S3, evenly mix tetraethyl orthosilicate and ethanol to obtain liquid A with a concentration of 0.5 mol / l of tetraethyl orthosilicate, evenly mix ammonia water and ethanol to obtain liquid B with a concentration of 0.8 mol / l of ammonia water, mix liquid A and liquid B, react at 25°C for 4 hours, and then age at 60°C for 24 hours to obtain silica sol; evenly mix polyethylene fiber and 10g of aluminum silicate fiber and then needle-punch to obtain a sol with a surface density of 200g / m 2 , placing the needle felt in silica sol, supercritical drying, and crushing to obtain fiber-reinforced aerogel powder, with a supercritical pressure of 12 MPa and a supercritical temperature of 270°C; S4, spraying fiber-reinforced aerogel powder on the endoderm, raising the temperature to 150° C., and keeping the temperature for 3 hours to obtain an intermediate layer on the endoderm, and the spraying amount of the fiber-reinforced aerogel powder is such that the thickness of the intermediate layer is 0.5 of the thickness of the endoderm; S5, mixing 10 g of wollastonite glass powder and fluoroapatite glass powder in a mass ratio, and heating until melted to obtain a melt; S6. Inject the melt into the mold, put the inner body with the intermediate into the mold, the melt adheres to the middle layer, and then perform secondary annealing and cooling to form a protective layer on the middle layer to obtain an explosion-proof glass bottle. The secondary annealing process is: keep warm at 580°C for 18 minutes, then cool down to 330°C at a rate of 6°C / min, keep warm for 160 minutes, cool down to 180°C at a rate of 6°C / min, keep warm for 70 minutes, and finally cool down to 120°C at a rate of 6°C / min, and keep warm for 160 minutes.

[0043] Example 4: An explosion-proof glass bottle, which differs from Example 1 in that the thickness ratio of the intermediate layer to the inner body is 0.2:1, and in step S4, the spraying amount of the fiber-reinforced aerogel powder is such that the thickness is 0.2 times the thickness of the inner body.

[0044] Example 5: An explosion-proof glass bottle, which differs from Example 1 in that the thickness ratio of the intermediate layer to the inner body is 0.8:1, and in step S4, the spraying amount of the fiber-reinforced aerogel powder makes the thickness 0.8 times the thickness of the inner body.

[0045] Embodiment 6: An explosion-proof glass bottle, which is different from Embodiment 1 in that, in step S4, after the polyethylene fiber and the aluminum silicate fiber are evenly mixed, the following pretreatment is performed before needling: 6.25 g of carboxymethyl cellulose was added to a mixture of anhydrous ethanol and distilled water, and polyvinyl alcohol was added after stirring for 15 min. The temperature was raised to 80° C. and stirred for 1 h to obtain a treatment solution. The mass ratio of carboxymethyl cellulose to polyvinyl alcohol was 2.5:1, and the mass ratio of carboxymethyl cellulose to anhydrous ethanol and distilled water was 6.25:3:50. Add the uniformly mixed polyethylene fiber and aluminum silicate fiber into the treatment liquid, stir evenly and filter, dry at 80°C for 8h, the mass ratio of aluminum silicate fiber to carboxymethyl cellulose is 1:0.625.

[0046] Embodiment 7: An explosion-proof glass bottle, which is different from Embodiment 1 in that, in step S4, the polyethylene fiber and the aluminum silicate fiber are mixed evenly and then subjected to the following pretreatment before being needled: 5 g of carboxymethyl cellulose was added to a mixture of anhydrous ethanol and distilled water, and polyvinyl alcohol was added after stirring for 10 min. The temperature was raised to 70° C. and stirred for 2 h to obtain a treatment solution. The mass ratio of carboxymethyl cellulose to polyvinyl alcohol was 5:2, and the mass ratio of carboxymethyl cellulose to anhydrous ethanol and distilled water was 5:2:40. Add the uniformly mixed polyethylene fiber and aluminum silicate fiber into the treatment liquid, stir evenly and filter, dry at 70°C for 10 hours, the mass ratio of aluminum silicate fiber to carboxymethyl cellulose is 1:0.5.

[0047] Embodiment 8: An explosion-proof glass bottle, which is different from Embodiment 7 in that phenolic fiber and low-melting-point glass powder are further added to the protective layer, the mass ratio of phenolic fiber, low-melting-point glass powder and wollastonite glass powder is 0.4:0.2:1, the low-melting-point glass powder is selected from Guangdong Qichen New Material Technology Co., Ltd., and the item number is D233, the phenolic fiber is made by mixing phenolic resin, polyvinyl butyral and anhydrous ethanol in a mass ratio of 4:0.035:7, and then electrospinning and heating to cure it, the phenolic resin is selected from Hebei Zetian Chemical, the item number is 2123, the brand is ZT, the polyvinyl butyral is selected from Guangzhou Qihua Chemical, the model is B17HX, during electrospinning, the needle The distance between the collecting plate is 15 cm, the spinning voltage is 25 kV, the spinning speed is 1 ml / h, and the heating curing method is: keeping warm at 70°C for 5 minutes, heating to 80°C at a rate of 10°C / min, keeping warm for 4 minutes, heating to 90°C at a rate of 10°C / min, keeping warm for 4 minutes, then heating to 100°C at a rate of 10°C / min, keeping warm for 2 minutes, and then heating to 120°C at a rate of 10°C / min, keeping warm for 5 minutes; the difference in the preparation method is that phenolic fiber, low melting point glass powder, silica glass powder and fluoroapatite glass powder are mixed and heated to melt to obtain a melt, and the rest of the method is the same as Example 7.

[0048] Embodiment 9: An explosion-proof glass bottle, which is different from Embodiment 7 in that phenolic fiber and low-melting-point glass powder are further added to the protective layer, the mass ratio of phenolic fiber, low-melting-point glass powder and wollastonite glass powder is 0.2:0.1:1, the low-melting-point glass powder is selected from Guangdong Qichen New Material Technology Co., Ltd., and the item number is D233, the phenolic fiber is made by mixing phenolic resin, polyvinyl butyral and anhydrous ethanol in a mass ratio of 4:0.03:6, and then electrospinning and heating to cure, the phenolic resin is selected from Hebei Zetian Chemical, the item number is 2123, the brand is ZT, the polyvinyl butyral is selected from Guangzhou Qihua Chemical, the model is B17HX, during electrospinning, the gap between the needle and the collecting plate The distance is 15 cm, the spinning voltage is 25 kV, the spinning speed is 1 ml / h, and the heating and curing method is: keep warm at 70°C for 5 minutes, heat to 80°C at a rate of 10°C / min, keep warm for 4 minutes, heat to 90°C at a rate of 10°C / min, keep warm for 4 minutes, then heat to 100°C at a rate of 10°C / min, keep warm for 2 minutes, then heat to 120°C at a rate of 10°C / min, and keep warm for 5 minutes; the difference in the preparation method is that in step S6, before the melt is injected into the mold, the inner surface of the mold is first sprayed with a uniform mixture of phenolic fiber and low-melting point glass powder, and then the melt is injected and the inner embryo with the intermediate layer is placed in the mold.

[0049] Embodiment 10: An explosion-proof glass bottle, which is different from Embodiment 7 in that phenolic fiber and low-melting-point glass powder are further added to the protective layer, the mass ratio of phenolic fiber, low-melting-point glass powder and wollastonite glass powder is 0.4:0.2:1, the low-melting-point glass powder is selected from Guangdong Qichen New Material Technology Co., Ltd., and the item number is D233, the phenolic fiber is made by mixing phenolic resin, polyvinyl butyral and anhydrous ethanol in a mass ratio of 4:0.035:7, and then electrospinning and heating to cure it, the phenolic resin is selected from Hebei Zetian Chemical, the item number is 2123, the brand is ZT, the polyvinyl butyral is selected from Guangzhou Qihua Chemical, the model is B17HX, during electrospinning, the needle head and the collecting plate are The distance is 15cm, the spinning voltage is 25kV, the spinning speed is 1ml / h, and the heating curing method is: keeping warm at 70℃ for 5min, heating to 80℃ at a rate of 10℃ / min, keeping warm for 4min, heating to 90℃ at a rate of 10℃ / min, keeping warm for 4min, then heating to 100℃ at a rate of 10℃ / min, keeping warm for 2min, then heating to 120℃ at a rate of 10℃ / min, keeping warm for 5min; the difference between the preparation methods is that, in step S6, before the melt is injected into the mold, the inner surface of the mold is first sprayed with a uniform mixture of phenolic fiber and low-melting point glass powder, and then the melt is injected and the inner embryo with the intermediate layer is placed in the mold.

[0050] Example 11: An explosion-proof glass bottle, which differs from Example 10 in that no low-melting-point glass powder is added to the protective layer, and only phenolic fiber is added, and the remaining parameters are the same as those of Example 10.

[0051] Comparative Example Comparative Example 1: An explosion-proof glass bottle. The difference from Example 1 is that no protective layer is provided, and the endoderm with the middle layer is the explosion-proof glass bottle product.

[0052] Comparative Example 2: An explosion-proof glass bottle, which differs from Example 1 in that no silica aerogel is added to the raw materials of the middle layer, and aluminum silicate fiber and polyethylene fiber are mixed evenly, needle-punched to obtain needle-punched felt, which is then attached to the inner embryo, and then heated to 160°C and kept warm for 2 hours to obtain the middle layer.

[0053] Comparative Example 3: An explosion-proof glass bottle, which differs from Example 1 in that polyethylene fiber and silica aerogel are not added to the raw materials of the middle layer, and the aluminum silicate fiber is needle-punched to obtain a needle-punched felt, which is attached to the inner embryo, and then heated to 160°C and kept warm for 2 hours to obtain the middle layer.

[0054] Comparative Example 4: An explosion-proof glass bottle, which differs from Example 1 in that an equal amount of polyethylene fiber is used in place of aluminum silicate fiber in the raw material of the middle layer.

[0055] Comparative Example 5: An explosion-proof glass bottle, which differs from Example 1 in that the middle layer is formed by uniformly mixing aluminum silicate fiber, polyethylene oxide fiber and silica aerogel, spraying the mixture on the inner embryo, and then heating the mixture to 160°C and keeping the mixture warm for 2 hours to obtain the middle layer. The silica aerogel is selected from Lingshou County Jinyuan Mining Processing Plant, with the item number 336.

[0056] Performance testing The performance of the glass bottle was tested according to the following method and the test results were recorded in Table 1.

[0057] 1. Impact strength: Test according to GB / T6552-2015 "Mechanical impact test method for glass bottles".

[0058] 2. Bending strength: Tested in accordance with GB / T37781-2019 "Test method for bending strength of glass materials".

[0059] 3. Self-explosion rate: Test in accordance with GB / T30020-2023 "Glass defect detection method - photoelastic scanning method".

[0060] 4. Surface compressive stress: Test in accordance with GB / T18144-2000 "Glass Stress Test Method".

[0061] Table 1 Performance test results of explosion-proof glass bottles From the test data in Examples 1-3 and Table 1, it can be seen that using cordierite or the like to prepare the endoderm, using aluminum silicate fiber, polyethylene fiber and silica aerogel to prepare the middle layer, and using wollastonite glass powder and fluoroapatite glass powder to make the protective layer can effectively enhance the impact strength of the glass bottle, reduce the self-explosion rate, improve the anti-explosion effect of the glass bottle, and improve the safety of use.

[0062] Compared with Example 1, Examples 4 and 5 reduce and increase the thickness of the middle layer, respectively. From the comparison of the data in Table 1, it can be seen that the impact resistance of the glass bottle prepared in Example 4 decreases, the bending resistance increases slightly, but the spontaneous explosion rate increases. Although the impact resistance of the glass bottle in Example 5 increases, the bending resistance weakens, and the spontaneous explosion rate increases.

[0063] Compared with Example 1, Example 6 and Example 7 further subjected the aluminum silicate fiber and polyethylene fiber used in the middle layer to surface treatment, and their self-explosion rates were reduced, and their impact strength, bending strength and surface compressive stress were slightly increased, indicating that surface treatment can further improve the overall mechanical strength of the glass bottle.

[0064] In Example 8, phenolic fiber and low-melting-point glass powder are added to raw materials such as wollastonite glass powder, and a melt is obtained after hot melting. The melt is then poured into a mold and adheres to the middle layer to form a protective layer. It can be seen that the impact resistance and explosion resistance of the glass bottle are slightly increased.

[0065] Compared with Example 7, Examples 9 and 10 further use phenolic fiber and low-melting-point glass powder as a protective layer outside the middle layer. The data in Table 1 show that the glass bottles prepared in Examples 8 and 9 have improved impact resistance, a slightly reduced self-explosion rate, increased surface compressive stress, and enhanced burst resistance.

[0066] Compared with Example 10, Example 11 does not add low-melting point glass powder, and only uses phenolic fiber. It can be seen that the impact resistance of the glass bottle prepared in Example 11 is slightly reduced.

[0067] Compared with Example 1, Comparative Example 1 does not set a protective layer, and only uses an endoderm containing an intermediate layer as a glass bottle product. From the data in Table 1, it can be seen that the impact strength of the glass bottle prepared in Comparative Example 1 decreases, the self-explosion rate increases, and the anti-explosion ability is significantly weakened.

[0068] Compared with Example 1, in Comparative Example 2, no silica aerogel is added to the middle layer. Only needle-punched felt formed by needle-punching a mixture of aluminum silicate fiber and polyethylene fiber is used to form the middle layer by bonding and heating. It can be seen that the explosion-proof ability of the glass bottle is reduced, the impact strength is weakened, and the self-explosion rate is increased.

[0069] In Comparative Example 3, polyethylene fiber and silica aerogel were not added. Aluminum silicate fiber was needle-punched and then bonded to the endoderm. It can be seen that various detection performances of the glass bottle were significantly reduced, indicating that the failure to add polyethylene fiber would make it difficult for aluminum silicate fiber to bond, resulting in deterioration of various performances of the glass bottle.

[0070] In Comparative Example 4, polyethylene fiber is used instead of aluminum silicate fiber. The polyethylene fiber is impregnated with silica sol after needle punching and supercritically dried to obtain fiber-reinforced aerogel powder. By comparison, it can be seen that the impact resistance of the glass bottle in Comparative Example 4 decreases and the self-explosion rate increases. Polyethylene fiber used alone will melt at high temperature and it is difficult to form a better reticular layer to protect the endoderm.

[0071] Compared with Example 1, Comparative Example 5 uses aluminum silicate fiber, polyethylene fiber and silica aerogel as raw materials, but the method of forming the middle layer is to mix the three raw materials and spray them on the inner embryo, and no needling of the two fibers and impregnation with silica sol are performed. It can be seen that the impact strength, bending strength and other properties of the glass bottle prepared in Comparative Example 5 are reduced compared with those in Example 1.

[0072] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. An explosion-proof glass bottle, characterized in that: It comprises an endomorph, an intermediate layer and a protective layer which are contacted from the inside to the outside in sequence, wherein the raw materials of the endomorph include cordierite, bismuth oxide and AIN ceramic powder in a mass ratio of 1:0.03-0.05:0.2-0.4; The raw materials of the intermediate layer include aluminum silicate fiber, polyethylene fiber and silica aerogel in a mass ratio of 1:0.3-0.4:10-15; The raw materials of the protective layer include wollastonite glass powder and fluoroapatite glass powder in a mass ratio of 1:0.2-0.

3.

2. The explosion-proof glass bottle according to claim 1, characterized in that: The thickness ratio of the intermediate layer to the endoderm is 0.4-0.6:

1.

3. The explosion-proof glass bottle according to claim 1, characterized in that: The length of the polyethylene fiber is 10-12 mm, and the length of the aluminum silicate fiber is 15-20 mm.

4. The explosion-proof glass bottle according to claim 1, characterized in that: Phenolic fiber and low-melting-point glass powder are also added to the protective layer, and the mass ratio of the phenolic fiber, the low-melting-point glass powder and the wollastonite glass powder is 0.2-0.4:0.1-0.2:

1.

5. The explosion-proof glass bottle according to claim 4, characterized in that: The phenolic fiber is prepared by mixing phenolic resin, polyvinyl butyral and anhydrous ethanol in a mass ratio of 4:0.03-0.035:6-7, electrostatic spinning and heating and curing.

6. The process for preparing the explosion-proof glass bottle according to any one of claims 1 to 3, characterized in that: The following steps are involved: The cerium oxide and cordierite are melted at 1500-1560°C for 2-4 hours, quenched with water, dried, ball-milled, and sieved to obtain a powder, which is mixed with AIN ceramic powder and heated until melted to obtain a hot melt; The hot melt is poured into the mold, blown into shape, and annealed once to obtain an endoderm; The polyethylene fiber and the aluminum silicate fiber are mixed evenly and needle-punched to obtain a needle-punched felt, and the needle-punched felt is placed in a silica sol, supercritically dried, and crushed to obtain a fiber-reinforced aerogel powder; Spraying fiber-reinforced aerogel powder on the endoderm, heating to 140-160° C., and keeping the temperature for 2-4 hours to obtain an intermediate layer on the endoderm; The wollastonite glass powder and the fluoroapatite glass powder are uniformly mixed and heated until they are melted to obtain a melt; The melt is injected into the mold, and the endoderm with the middle layer is placed in the mold. The melt adheres to the middle layer, and then secondary annealing and cooling are performed to form a protective layer on the middle layer to produce an explosion-proof glass bottle.

7. The method for preparing an explosion-proof glass bottle according to claim 6, characterized in that: The polyethylene fiber and aluminum silicate fiber are subjected to the following pretreatment before needling: Add carboxymethyl cellulose to a mixture of anhydrous ethanol and distilled water, stir for 10-15 minutes, add polyvinyl alcohol, heat to 70-80°C, stir for 1-2 hours, and prepare a treatment solution; Add the uniformly mixed polyethylene fiber and aluminum silicate fiber to the treatment liquid, stir evenly, filter, and dry at 70-80°C for 8-10 hours. The mass ratio of aluminum silicate fiber to carboxymethyl cellulose is 1:0.5-0.

625.

8. The method for preparing an explosion-proof glass bottle according to claim 6, characterized in that: Before the melt is injected into the mold, evenly mixed phenolic fiber and low-melting-point glass powder are sprayed onto the inner surface of the mold, and the mass ratio of the phenolic fiber, the low-melting-point glass powder and the wollastonite glass powder is 0.2-0.4:0.1-0.2:

1.

9. The method for preparing an explosion-proof glass bottle according to claim 6, characterized in that: The surface density of the needle felt is 180-200 g / m 2 .

10. The method for preparing an explosion-proof glass bottle according to claim 6, characterized in that: The secondary annealing process is: keeping the temperature at 550-600°C for 15-20min, then cooling to 300-350°C at a speed of 4-8°C / min, keeping the temperature for 120-200min, cooling to 150-200°C at a speed of 4-8°C / min, keeping the temperature for 60-80min, and finally cooling to 100-130°C at a speed of 4-8°C / min, keeping the temperature for 120-180min.